Relationships Between the Posterior Interosseous Nerve and the Supinator Muscle: Application to Peripheral Nerve Compression Syndromes and Nerve Transfer Procedures - Tubbs, R. Shane; Mortazavi, Martin M.; Farrington, Woodrow J.; Chern, Joshua J.; Shoja, Mohammadali M.; Loukas, Marios; Cohen-Gadol, Aaron A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Study Aims Little information can be found in the literature regarding the relationships of the posterior interosseous nerve (PIN) while it traverses the supinator muscle. Because compression syndromes may involve this nerve at this site and researchers have investigated using branches of the PIN to the supinator for neurotization procedures, the authors' aim was to elucidate information about this anatomy.Materials and Methods Dissection was performed on 52 cadaveric limbs to investigate branching patterns of the PIN within the supinator muscle.Results On 29 sides, the PIN entered the supinator muscle as a single nerve and from its medial side provided two to four branches to the muscle. On 23 sides, the nerve entered the supinator muscle as two approximately equal-size branches that arose from the radial nerve on average 2.2 cm from the proximal edge of this muscle. In these cases, the medial of the two branches terminated on the supinator muscle, and the lateral branch traveled through the supinator muscle; in 13 specimens, it provided additional smaller branches to the supinator muscle. The length of PIN within the supinator muscle was 4 cm on average, and the diameter of its branches to the supinator muscle ranged from 0.8 to 1.1 mm. In 10 specimens, the PIN left the supinator muscle before the most distal aspect of the muscle. In two specimens with a single broad PIN, muscle fibers of the supinator muscle pierced the PIN as it traveled through it.Conclusion This knowledge of the anatomy of the PIN as it passes through the supinator muscle may be useful to neurosurgeons during decompressive procedures or neurotization.
Keywords: anatomy; compression; neurosurgery; peripheral nerve; upper limb